Lehman, Bloodshed At Little Bighorn - Sitting Bull, Custer, And The Destinies Of Nations - Bremar, Jeff (Teaching History: A Journal of Methods, 2010)
Lehman's new book on the most famous battle in the American West is a useful and extremely readable narrative of Custer's defeat and a fine introduction to the long conflict between the expansionist United States and the native tribes of the Great Plains. Bloodshed at Little Bighorn is a concise, clearly written account that deftly traces the history of the long series of clashes that led up to this battle. This engaging monograph is ideal for use in undergraduate classrooms, as the author provides gracefully crafted portraits of important characters and reviews important ideas, from American military strategy to the importance of the horse for Plains tribes. Non-specialists will find that Lehman 's book is a fine summary of the final American conquest of the American West. While it includes no new interpretation and relies heavily on secondary sources, it provides a balanced, fast paced history ideal for use in survey courses on the West, Native America, or the nineteenth-century United States. It is also a good source for material for anyone writing or revising lectures on the subject.